BUDAYA PERJUMPAAN: Jalan-jalan (Baru) Dialog Antar Umat Beragama - HS, P Banyu Dewa (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2022)
The Covid-19 pandemic has not only damaged health, but has also torn apart all aspects of life, both in the economic, educational, social and even religious fields. The impacts of the pandemic that are being felt include increasing unemployment, rising poverty, delays in the process of education and office work. All of this is not only frightening, but also brings hope and our future to fade. In this time of a pandemic that hasn't completely ended, people should unite, join hands to contain the rate of spread and alleviate the suffering of those affected. Personal and group egoism, greed, mutual suspicion, hatred and enmity are attitudes that make our struggle against corona not produce significant results. Pope Francis in Fratelli Tutti reminds people from all walks of life and groups about the importance of cultivating a spirit of brotherhood. Among the citizens, the spirit of brotherhood can be realized by developing a culture of gotong royong, a civilization of love to relieve one another's suffering and inflame optimism. Srawung culture, is one of the instruments towards true brotherhood, because srawung culture not only develops family ties, but also creativity to build bridges of peace. The more teams collaborate, the process of inter-religious co-formation is very possible for the journey towards changing the way of life of religion in a plural society.